Comparison of Islamic Law and Human Rights; Navigating Consensus of LGBT in Thailand - Aidatul Fitriyah; Muhammad Badat Alauddin (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2024)
This research aims to examine the dynamics of law and human rights (HAM) related to the LGBT community in Thailand, with a focus on analysing the concept of Islamic epistemology on the social status impact of the idea of gender division in Thailand, theological and juridical comparison of human rights in accommodating LGBT, as well as challenges and efforts to harmonise Islamic law and human rights towards LGBT groups in Thailand. The methodology used is a qualitative approach involving normative and comparative legal analysis. The researcher collected a literature review of secondary data from relevant sources, including scholarly works, books, and legal documents. The results showed significant contradictions between Thailand's more inclusive concept of gender division and the binary nature of Islamic law. The research also uncovered Islamic theological underpinnings against LGBT and compared them with juridical approaches that protect LGBT human rights. It also explores the reconciliation process between Islamic law and human rights in accommodating LGBT through dialogue and stakeholder cooperation. From this research, it can be concluded that LGBT law and human rights tolerance involve a complexity of legal views, religious values, and human rights principles, reflecting ongoing challenges and debates within society and the legal system.